Living donor liver transplantation in maple syrup urine disease – Case series and world's youngest domino liver donor and recipient. (12th February 2016) - Mohan, N.; Karkra, S.; Rastogi, A.; Vohra, V.; Soin, A. S.
Abstract: MSUD occurs due to deficiency of enzyme BCKAD required for metabolism of leucine, isoleucine, and valine leading to the accumulation of these and their ketoacids causing acute metabolic decompensation manifesting as encephalopathy or sudden death. The patient requires special protein‐restricted diet to survive. As this enzyme is expressed in liver, liver transplantation has been successfully performed as a cure. We report two patients of MSUD who underwent LDLT while their livers were used as a domino graft for other biliary cirrhotic patients. A 22‐month‐old male child diagnosed as a case of classic MSUD underwent LDLT from an altruistic aunt as donor following which his serum leucine levels normalized on an unrestricted protein diet. His liver was used as a domino graft. A 38‐month‐old female child with diagnosed MSUD underwent LDLT from a swap donor, and her liver was used as a domino graft. Her DQ improved post‐transplant. LDLT from non‐heterozygous donors is a cure for classical MSUD. Their livers can be used as domino grafts for non‐MSUD cases.